The Southeast Asian genus Stedocys Ono, 1995 (Araneae: Scytodidae): first descriptions of female genitalia and a new species from China - Labarque, Facundo M.; Grismado, Cristian J.; Ramírez, Martín J.; Yan, Hengmei; Griswold, Charles E. (Zootaxa, 2009)
The genus Stedocys was known only from males. Here we describe the first females of the genus. Stedocys genitalia are atypical for Scytodidae. Males are distinguished by having the papal tarsus subequal or smaller than the tegulum, not prolonged apically, without prolateral blunt macrosetae; the tegulum long, inserted apically on the tarsus; embolus slightly shorter than bulb, aciculate distally, and females by lacking fovea or positioning ridges below the epigastric furrow, and by having an anterior epigynal pouch. In this contribution, we describe the female and redescribe the male of Stedocys leopoldi (Giltay, 1935), and describe male and female of Stedocys pagodas new species from China (Yunnan). The lack of a projection on the male palpal tarsus suggests that Stedocys is the sister group of all other genera of Scytodidae.